Investigating Pregnancy and Its Complications Using Circulating Cell-Free RNA in Women's Blood During Gestation - Moufarrej, Mira N.; Wong, Ronald J.; Shaw, Gary M.; Stevenson, David K.; Quake, Stephen R. (Frontiers in Pediatrics, 2020)
In recent years, there have been major advances in the application of non-invasive techniques to predict pregnancy-related complications, for example by measuring cell-free RNA (cfRNA) in maternal blood. In contrast to cell-free DNA (cfDNA), which is already in clinical use to diagnose fetal aneuploidy, circulating RNA levels can correspond with tissue-specific gene expression and provide a snapshot of prenatal health across gestation. Here, we review the physiologic origins of cfRNA and its novel applications and corresponding challenges to monitor fetal and maternal health and predict pregnancy-related complications.